Sintasan Dan Pertumbuhan Larva Ikan Ikan Lele (Clarias sp) Hasil Penetasan Telur Melalui Penambahan Madu Dalam Pengenceran Sperma - Mambrasar, Pulinus; Monijung, Revol; Kalesaran, Ockstan; Watung, Juliaan Ch (Universitas Sam Ratulangi, 2015)
The purposes of research were to determine the survival and growth of catfish larvae (Clarias sp) produced from eggs using honey in sperm dilution.Â Sperm dilution was prepared by disolving honey (0 mL; 0,6 mL; 0,65 mL; dan 0,7 mL) in 100 mL, 99,4 mL; 99,35 mL dan 99,3 mL NaCl respectively. The research was conducted using Complete Randomized Design (CRD) with four treatments each with three replications. Research results showed that survival of larvae at treatment D was the highest (81,33%), followed by treatment C (75%) and B (72%) and the lowest was treatment A (63.67%). The highest absolute length growth was achieved at treatment D (1.73 cm) followed by treatment C (1.40 cm), B (1.10 cm) and the lowest was treatment A (1.03 cm). It could be concluded that supplementation of honey in sperm dilution influenced the survival and growth of catfish larvae Keywords: honey, Clarias sp, sperm dilution, survival, growth